Ideologies of Corporate Responsibility: From Neoliberalism to "Varieties of Liberalism". Issue 4 (10th October 2022) - Vallentin, Steen; Murillo, David
Abstract : Critical scholarship often presents corporate social responsibility (CSR) as a reflection or embodiment of neoliberalism. Against this sort of sweeping political characterization we argue that CSR can indeed be considered a liberal concept but that it embodies a "varieties of liberalism." Building theoretically on the work of Michael Freeden on liberal languages, John Ruggie and Karl Polanyi on embedded forms of liberalism, and Michel Foucault on the distinction between classical liberalism and neoliberalism, we provide a conceptual treatment and mapping of the ideological positions that constitute the bulk of modern scholarly CSR debate. Thus, we distinguish between embedded liberalism, classical liberalism, neoliberalism, and re-embedded liberalism. We develop these four orientations in turn and show how they are engaged in "battles of ideas" over the meaning and scope of corporate responsibilities—and how they all remain relevant for an understanding of contemporary debates and developments in the field of CSR and corporate sustainability.